In situ reconstruction of distal renal artery aneurysm - I.I. Kobza; H.D. Roiko; H.Yu. Orel; О.S. Shchepitko (Медицина неотложных состояний)
Renal artery aneurysm (RAA) is a rare disease that occurs in 0.1 % of the general population. The risk of a rupture of RAA is generally low, about 5 %; however, it increases rapidly with the aneurysm size over 2 cm and is accompanied by a very high mortality (more than 80 %). Choosing a treatment strategy for managing patients with RAA and a personalized approach in each clinical case, based on the assessment of clinical and anamnestic features of the patient and the morpho-functional characteristics of the aneurysm, remains an urgent problem today. The purpose of our publication is to review a clinical case of a distal renal artery aneurysm with successful in situ reconstruction.